A critical review on the chemical wear and wear suppression of diamond tools in diamond cutting of ferrous metals. (14th January 2020) - Jiang, Guo; Jianguo, Zhang; Yanan, Pan; Renke, Kang; Yoshiharu, Namba; Paul, Shore; Xiaobin, Yue; Baorui, Wang; Dongming, Guo
Abstract: Diamond tools play a critical role in ultra-precision machining due to their excellent physical and mechanical material properties, such as that cutting edge can be sharpened to nanoscale accuracy. However, abrasive chemical reactions between diamond and non-diamond-machinable metal elements, including Fe, Cr, Ti, Ni, etc, can cause excessive tool wear in diamond cutting of such metals and most of their alloys. This paper reviews the latest achievements in the chemical wear and wear suppression methods for diamond tools in cutting of ferrous metals. The focus will be on the wear mechanism of diamond tools, and the typical wear reduction methods for diamond cutting of ferrous metals, including ultrasonic vibration cutting, cryogenic cutting, surface nitridation and plasma assisted cutting, etc. Relevant commercially available devices are introduced as well. Furthermore, future research trends in diamond tool wear suppression are discussed and examined.